Mentoring network and self-monitoring personality - Seong-kook Kim; Min-jeong Kim (Management Revue, 2007)
Combining mentoring theory with social network theory, this study investigates the formation of mentoring networks. In a sample of 127 military officers, we test hypotheses regarding the relationship between self-monitoring personality and mentoring network characteristics. Protégé's self-monitoring orientation predicted the tie strength in his or her mentoring network. Results support the statement that personality variables predict the structure of social networks. In addition, results of the social network analysis confirm that individuals receive mentoring assistance from multiple mentors and that the mentoring network characteristics a protégé possesses differ depending on his/her self-monitoring orientation.
Keywords: 650; mentoring network; self-monitoring; social network; personality; Personalentwicklung; Soziales Netzwerk